Acid-Base Ideas Among Libyan Undergraduate Seniors: A Phenomenological Approach - Amani Abdugadar, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
Exploring students' ideas about a particular concept is the first step in the process of constructing valid diagnostic instruments such as concept inventories and multi-tier tests. This exploratory qualitative study, utilizing a phenomenological approach, aimed to investigate Libyan undergraduate chemistry seniors' conceptual understanding and identify misconceptions regarding acid-base chemistry. The study was conducted at a public university in eastern Libya, involving five senior chemistry majors who had completed Analytical Chemistry (I). Participants engaged in a guided-inquiry, project-based learning experience where they designed laboratory experiments and reported their findings. Data collection involved multiple methods, including observations during discussions and laboratory sessions, a demographic questionnaire, an open-response test with a confidence-level reporting section, and in-depth interviews. Thematic analysis was employed to identify patterns and clusters of ideas from transcribed interviews. The results revealed several significant misconceptions, some of which had not been previously documented in literature. Notable findings included participants' inability to draw titration curves for weak acid-weak base systems, confusion between hydronium ion concentration and pH values, and the misconception that an indicator acts as a catalyst. Furthermore, some students incorrectly defined Brønsted acids based on electron gain rather than proton transfer. Participants reported that the hands-on activities and the project-based approach significantly improved their understanding and prepared them for their final reports. The study concludes that identifying these specific misconceptions is vital for educators to improve teaching strategies and develop more effective diagnostic assessments.
Keywords: Chemistry education; teaching acid-base chemistry; Upper-division undergraduates; students’ pre-concepts; project-based learning